Systemic Anaplastic Large T-Cell Lymphoma with Initial Presentation of Dysuria in a Dog. (November 2021) - Kaneguchi, Ayumi; Izawa, Takeshi; Tanaka, Miyuu; Suzuki, Hirofumi; Tani, Hiroyuki; Kuwamura, Mitsuru; Yamate, Jyoji
Summary: A 6-year-old spayed female Akita Dog had dysuria, severe urinary retention and miliary masses in the vagina. Computed tomography revealed a mass at the urethrovaginal junction. The dog died 2 months after initial presentation. At necropsy, the urethrovaginal mass was greyish‒white, solid and 9 × 6 × 6 cm in size with circumferential thickening of the urethral wall. Multiple whitish nodules were seen in the visceral organs and skin. Histopathologically, the urethrovaginal mass comprised a diffuse population of medium-sized to large round neoplastic cells with ovoid to bean-shaped nuclei and eosinophilic cytoplasm. Aberrantly large neoplastic cells with eccentric, horseshoe-shaped or irregularly-shaped nuclei and abundant eosinophilic cytoplasm resembled 'hallmark cells' of human anaplastic large cell lymphoma. Similar neoplastic lesions were present in all the grossly visible masses. Neoplastic cells were diffusely immunopositive for CD3 and occasionally for CD30 and granzyme B. On the basis of the clinical, pathological and immunohistochemical findings, the case was diagnosed as systemic anaplastic large cell lymphoma arising from the lower urinary tract.